The belief on the law of karma moderates the effect of idealism and professional commitment on the ethical decisions of tax consultants - Vinayanthi, Ni Made; Wirakusuma, Made Gede; Suprasto, Herkulanus Bambang; Putri, I G A M Asri Dwija (International research journal of management, IT and social sciences, 2020)
Ethical decision is a decision that is both legally and morally that can be accepted by the wider community. The importance of ethical decisions is taken in solving problems experienced effectively, so that decisions taken do not violate applicable norms and can be accepted by the wider community. The purpose of this study is to find out and obtain empirical evidence about the role of belief in the law of karma in moderating the influence of idealism and professional commitment to the ethical decisions of tax consultants. The population in this study are all registered tax consultants in the Province of Bali. This research analysis technique uses Moderate Regression Analysis (MRA). Based on the results of the analysis it was found that idealism has a positive effect on the ethical decisions of tax consultants. Professional commitment has a positive effect on the ethical decisions of tax consultants. Belief in the law of karma reinforces the influence of idealism on the ethical decisions of tax consultants. Belief in the law of karma reinforces the influence of professional commitment on the ethical decisions of tax consultants.